The Effect of Preceived Organizational Support and Normative Commitment on Employee Performance in Moderation by Self Awareness - Ari Soeti Yani; Sri Juliati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is about the Effect of Preceived Organizational and Normative Commitment against Employee Performance Moderated by Self Awareness which was conducted at UTA 45 Jakarta. The total population studied in this study were all employees of UTA 45 Jakarta. The method of taking this sample is by using porpuse sampling by randomly distributing it to all employees. The research was conducted to determine how the influence of perceived organizational and normative commitment and moderating self awareness able to strengthen or weaken the influence organizational perceivers on employee performance and self awareness was able to strengthen or weaken the influence of normative commitment on employee performance through several stages, the first stage was taken from the literature. , descriptive statistics and collection of researched objects.tools software (PLS). Based on the objectives of the results to be achieved by the researchers as follows; organizational perceiver has no effect on employee performance, normative commitment has no effect on employee performance, self awareness has a significant effect on employee performance, moderated self awareness can weaken the influence organizational perceiver on employee performance, moderated self awareness can weaken the influence of normative commitment on employee performance.